Detecting, locating, and characterizing voids in disaster rubble for search and rescue. (October 2019) - Hu, Da; Li, Shuai; Chen, Junjie; Kamat, Vineet R.
Highlights: A novel method to detect, locate, and characterize voids in disaster rubble. An Innovative application of ground penetrating radar in search and rescue. A new means to augment first responders' situational awareness. An applicable system validated by simulations and scaled experiments. Abstract: After natural and man-made disasters such as earthquakes, hurricanes, and explosions, victims may survive in voids that are formed naturally in collapsed structures. First responders need to identify and locate these critical voids for rapid search and rescue operations. Due to the complex and unstructured occlusions in disaster areas, visual and manual search is time-consuming and error-prone. In this study, we proposed a novel method to automatically detect, locate, and characterize voids buried in disaster rubble using ground penetrating radar (GPR). After preprocessing the collected radargrams, the boundaries of potential voids are segmented based on radar signal patterns, and the 95% confidence intervals are constructed around the segmented boundaries to account for uncertainties. To improve the detection accuracy, the geometric relations of the detected boundaries and their signal characteristics are examined to confirm the void existence. Then, the void location and dimension are estimated based on calibrated velocity of radar wave and its travel time. The effectiveness and efficiency of the proposed method were manifested by its performance in laboratory and field experiments. The contribution of this study is twofold. First, the feasibility of using GPR to detect, locate, and characterize voids in collapsed structures is experimentally tested, innovatively extending the application of GPR to search and rescue operations. Second, algorithms are developed to process non-intuitive radargrams to provide first responders actionable information.